Structural and functional mechanisms of sustainable rural development in Kazakhstan through corporate social responsibility - Zhenskhan, Darima; Tokenova, Sandugash; Appazova, Gulbanu; Kypshakbayev, Bakdaulet; Azan, Tangat (International Journal of Innovative Research and Scientific Studies, 2025)
The aim of this study is to highlight the importance of corporate social responsibility (CSR) in strengthening the interaction among society, local entrepreneurship, the state, and rural residents within the framework of the structural and functional model (SFM). The study covers a 12-year period from 2010 to 2021 and focuses on data from the Zerendy and Korgalzhyn districts of the Akmola region, located in Northern Kazakhstan. The factors affecting the decline in the rural population were studied using spatial-temporal data, comparative analysis, correlation, and regression methods. Among the 45 indicators describing demographic, social, and economic factors, four key indicators were identified as directly influencing changes in the rural population of the two districts: the number of rural settlements with schools, the number of rural settlements with healthcare facilities, the number of hospital beds, and the number of doctors in rural areas. Integrating the SFM with the CSR mechanism enables the achievement of potential socio-economic outcomes for rural residents. To effectively implement programs aimed at improving rural living standards, curbing population decline, attracting young professionals, and developing local agricultural entrepreneurship, Kazakhstan should focus on structural mechanisms for implementing corporate social responsibility (CSR) through agricultural cooperatives.